A Typology of Drug Selling Among Young Adults in the United States. (23rd February 2015) - Vaughn, Michael G.; Salas-Wright, Christopher P.; DeLisi, Matt; Shook, Jeffrey J.; Terzis, Lauren
<x xml:space="preserve">Abstract</x> Background: Although studies have found that young adults who sell drugs are more likely to be involved in risky behaviors than those who do not sell drugs, there has been relatively little research that has explored heterogeneity among young adults who sell drugs. Methods: Using a pooled sample of 18 to 25 year olds from the National Survey on Drug Use and Health (2006–2010) who report past-year drug selling (N = 5, 373), this study employs latent profile analysis to specify latent groups and assess the correlates of group membership. Results: Findings indicate substantial differences among young adults who sell drugs. In particular, the analysis found four groups of drug sellers: normative (49.6%), club drug users (23.6%), polysubstance users (16.0%), and criminal offenders (10.8%). Club drug users were characterized by high levels of ecstasy and hallucinogen use, polysubstance users were more likely to be depressed and anxious, White and female than the other groups. Criminal offenders were overwhelmingly male and more likely to be comprised of African-Americans and Hispanics. Conclusions: Results indicate that drug selling in early adulthood varies substantially. Contrary to media and popular notions most drug sellers are not involved in crime and polysubstance using drug sellers are in clear need of mental health services. Further, most drug sellers in this age range are White. Findings suggest that policy efforts that operate under the assumption of homogeneity of drug selling may be misguided.